Retrieval induces reconsolidation of fear extinction memory - Rossato, Janine I. (2010)
The nonreinforced expression of long-tem memory may lead to two opposite protein synthesis-dependent processes: extinction and reconsolidation. Extinction weakens consolidated memories, whereas reconsolidation allows incorporation of additional information into them. Knowledge about these two processes has accumulated in recent years, but their possible interaction has not been evaluated yet. Here, we report that inhibition of protein synthesis in the CA1 region of the dorsal hippocampus after retrieval of fear extinction impedes subsequent reactivation of the extinction memory trace without affecting its storage or that of the initial fear memory. Our results suggest that extinction memory is susceptible to a retrieval-induced process similar to reconsolidation in the hippocampus.